Study on hot air heating characteristics of greenhouse in cold region - Zhang, Chenghu; Zou, Dezhi; Huang, Xinpeng; Wu, Yaling (Frontiers in Energy Research, 2023)
Agriculture is the main industry in northeast China. As an important part of facility agriculture, agricultural greenhouses are playing a more and more important role. Due to geographical location, Northeast China is cold in winter, and the solar radiation energy is less, therefore, the large-span greenhouses commonly used in northeast China are prone to uneven temperature and insufficient heating. In this paper, in order to solve the phenomenon of uneven air flow field, humidity field and temperature field in greenhouse, based on AIRPAK simulation, four kinds of hot air heating return air modes, such as upper air supply and lower air return mode, lower air supply and upper air return mode, two-side air supply mode and left air supply and right air return mode, we explored the influence of temperature field, humidity field and air flow field in greenhouse. The results showed that the heat load of the greenhouse in winter is 161.51 kW, using two-side air supply mode is the best way. The air supply wind speed is 1.6 m/s, and the return wind speed is 3.1 m/s. The environment of the greenhouse can be maintained at about 15°C day and night, and the relative humidity is relatively uniform. In the crop growing area, the wind speed is between 0 m/s and 0.25 m/s. According to this research, suitable crops can be selected for reasonable planting and distribution in the greenhouse to maximize productivity.